(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
This study assesses the impact of public programs supporting innovation and technological services on the business performance of Peruvian firms, using microdata from the National Innovation Survey in the Manufacturing Industry and Knowledge-Intensive Service Firms (Eniimesic) 2018 and the Inverse Probability Weighted Regression Adjustment (IPWRA) estimator. This doubly robust approach allows identifying causal effects of treatment under the conditional independence assumption. Results reveal a heterogeneous landscape: public programs significantly enhanced innovation and exports but did not lead to immediate improvements in domestic sales. On average, beneficiary firms exhibit a 19-percentage-point higher likelihood of introducing product or process innovations and more than a 100% increase in exports compared to non-beneficiaries. However, a 31% reduction in sales and a lower concentration of revenues in the main product are observed, suggesting productive diversification processes accompanied by short-term adjustments. When distinguishing by intervention type, innovation subsidies show stronger effects on product innovation and exports, while technological services primarily foster process innovation and diversification. These findings indicate a potential short-term trade-off between innovative activities and commercial performance. From a public policy perspective, the results highlight the need for better coordination among support instruments, stronger post-program follow-up, and the use of the upcoming ENIIMESIC 2025 survey to assess the persistence and sustainability of these effects.